Investigating the Antimicrobial Activity of Anuran Toxins - Manuela B. Pucca; Anne Grace A. C. Marques; Ana Flávia M. Pereira; Guilherme Melo-dos-Santos; Felipe A. Cerni; Beatriz C. S. Jacob; Isabela G. Ferreira; Rafael L. Piccolo; Marco A. Sartim; Wuelton M. Monteiro; Isadora S. Oliveira (Microorganisms)
Anurans, commonly known as frogs and toads, comprise a diverse group of amphibians distributed across all continents except Antarctica. This manuscript provides a detailed overview of the global anuran fauna, emphasizing their biology, remarkable adaptations, and ecological importance. A particular focus is placed on their specialized cutaneous glands, which are crucial for defense, communication, and survival. These glands secrete a diverse array of bioactive compounds, including peptides, alkaloids, and other secondary metabolites, shaped by evolutionary pressures. Among these compounds, toxins with potent antimicrobial properties stand out due to their ability to combat a broad spectrum of microbial pathogens. We explore the chemical diversity of these secretions, analyzing their modes of action and their potential applications in combating antibiotic-resistant bacteria and other pathogens. By integrating knowledge, this study underscores the importance of anurans as both ecological keystones and a valuable resource for biotechnological innovations. Furthermore, it highlights the urgent need to conserve anuran biodiversity for harnessing their potential in the development of novel antimicrobial agents to address global health challenges.